Review on Social Welfare Crowdfunding in China Based on PEST-SWOT Model - Jing Liang; Ao Chen (Complexity)
Research shows that social welfare crowdfunding is in the rising stage of development in China, showing a vigorous development trend. Social welfare crowdfunding owns advantages such as accuracy and efficiency that traditional social welfare forms do not have, but problems including imperfect relevant policies and regulations, lack of supervision of social welfare crowdfunding platform, and low process transparency still exist. From the perspective of PEST-SWOT model, this paper sums up the research trends and development status of social welfare crowdfunding, deconstructs the strengths, weaknesses, opportunities, and threats faced by social welfare crowdfunding from the aspects of politics, economy, society, and technology, and puts forward a feasible analysis of relevant development strategies to provide a reference for its future sustainable development.